Climbing Your Way To Wellness: A Review - Woźniak, Martyna; Słomianny, Marcela; Kutnik, Karolina; Kusibab, Karolina; Sikora, Gabriela; Czechowski, Michał; Gunia, Katarzyna; Koguc, Karolina; Kolada, Karolina; Sajda, Małgorzata (Quality in Sport, 2025)
Background: Bouldering is a rapidly growing sport with emerging evidence of health-promoting effects across physical, psychological, and social domains. Aim: To synthesize current research on the health benefits of bouldering and assess its potential as a preventive and therapeutic intervention. Methods: This paper reviews over 20 peer-reviewed studies, including randomized controlled trials, qualitative analyses, and mixed-methods research, examining bouldering’s effects on mental health, physical fitness, and social well-being. Results: Bouldering was associated with significant reductions in depression, anxiety, and stress, alongside improvements in self-efficacy and emotional regulation. Physical benefits included increased muscular strength, endurance, and improved body composition. Social gains involved enhanced connection, inclusion, and subjective well-being. Outcomes were comparable or superior to traditional exercise and therapeutic approaches in several studies. Conclusions: Bouldering is a holistic, accessible intervention that fosters integrated health benefits. Its unique combination of cognitive, physical, and social challenges supports its inclusion in health promotion and therapeutic settings.